Necrotizing enterocolitis: what is the role of social determinants of health - Jordan Stone; Maria Chimarios; Jaein Kim; Xue Zhou; Amy Chen; Catherine Kilada; Martine A. Louis; Nageswara Mandava (International Surgery Journal, 2026)
Background: Neonatal necrotizing enterocolitis (NEC) is a gastrointestinal emergency predominantly affecting premature and low-birth-weight infants. NEC mortality rates range from 20-40%, but can be as high as 100% in severe forms of the disease. Recent studies have examined social determinants of health (SDOH) in neonatal disease and emerging evidence suggests that they may also influence outcomes in NEC. This study aimed to evaluate the association between maternal socioeconomic disadvantage, measured by the Area Deprivation Index (ADI) and NEC in a community hospital setting (Queens, NY). We examined whether higher ADI levels in a diverse patient population were associated with disease presentation, severity index and adverse clinical outcomes. Methods: We conducted a single-center retrospective study at Flushing Hospital Medical Center in Queens, NY of 21 neonates diagnosed with NEC between October 2012 and 2024; neonates without a confirmed diagnosis of NEC during this period were excluded. Utilizing state ADI from the Neighborhood Atlas, neonates were categorized into less disadvantaged (ADI 5). Bivariate analysis determined differences among demographics and clinical characteristics, including maternal BMI and neonatal birth weight, laboratory values and treatments. IRB approval was obtained. Results: 21 neonates with NEC between 2012 and 2024 were studied, 9 females and 12 males, with a median gestational age of 24-25 weeks and 6 days. Twenty mothers had government-provided insurance. Among 21 neonates with NEC, 18 were categorized as less disadvantaged and 3 as more disadvantaged based on ADI. The more disadvantaged cohort showed a median birth weight of 600-699 g and less acidosis with a base deficit (BD -3.7-7.8) compared to the less disadvantaged cohort: BW 650-750 g and more acidosis with base deficit (-12.5-16.1). The more disadvantaged maternal cohort was younger (20-29 y), of Hispanic descent, with a higher BMI (34-37.9) and 33% positive for Group B Streptococcus (GBS). The less disadvantaged cohort had a median age of 30-39 y, BMI 30-33.9 and 27.8% positive for GBS. The neonates from the less disadvantaged cohort underwent surgical intervention more than the more disadvantaged, 38.9% versus 33%. Conclusions: Social determinants of health should be considered among risk factors associated with NEC. Surgeons may need to include them in their initial evaluation. We recognize that our small sample from a single center provided limited data, but replication could lead to earlier recognition and potentially improved outcomes.